Impact of anxiety and finance on academic performance among college students - Alexía Ýr Í. Christensen 1997- (2022)
Academic performance is certainly an important factor in student lives and their future employment. The main purpose of the present study was to investigate if academic performance is affected by anxiety and finance. Limited research has been conducted on anxiety and finance as the main influencing factors on academic performance in Iceland. A total of 467 college students at Reykjavik University participated in this study, 37.8% were males and 62.2% were females, between the ages of 18 to 65 years. Participants received an online questionnaire via mail and information was gathered on background, anxiety, and financial status. Using an ordinary least squares multiple regression a significant regression equation was found, participants predicted academic performance as equal to 3.629. The results demonstrated that anxiety, poor financial status, and working alongside education had a negative effect on academic performance and for that reason, all three hypotheses in this current study were confirmed. Anxiety was the strongest predictor of academic performance while working alongside education was the weakest predictor, although, all predictors were statistically significant. Keywords: Academic performance, anxiety, finance, students Námsárangur er vissulega mikilvægur þáttur í lífi nemenda og framtíðarstarfi þeirra. Helsta markmið rannsóknarinnar var að kanna hvort að kvíði og fjárhagur hafi áhrif á námsárangur. Takmarkaðar rannsóknir hafa verið gerðar á kvíða og fjárhag sem helstu áhrifaþætti námsárangurs á Íslandi. Alls tóku 467 nemendur í Háskólanum í Reykjavík þátt í rannsókninni, 37.8% voru karlar og 62.2% voru konur, á aldrinum 18 til 65 ára. Þátttakendur fengu rafrænan spurningalista í pósti og safnað var upplýsingum um bakgrunn, kvíða og fjárhagsstöðu nemenda. Með fjölbreytuaðhvarfsgreiningu fannst marktæk aðhvarfsjafna, þátttakendur spáðu 3.629 í námsárangri. Niðurstöðurnar sýndu að kvíði, léleg fjárhagsstaða og að vinna samhliða námi hafði neikvæð áhrif á námsárangur og af þeim sökum, voru allar þrjár ...